Sejauh Mana Partisipasi Perempuan Menentukan Kemakmuran Sosial-Ekonomi di Negara-Negara Muslim? Bukti dari Berbagai Kawasan - Muhammad Akbar Ramadhani; Basrian Basrian; Muhammad Noor Ashry (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
This study investigates the extent to which women's participation determines socioeconomic welfare, measured by the Human Development Index (HDI), in Muslim-majority countries, with particular attention to interregional heterogeneity. Utilizing panel data from 46 member states of the Organisation of Islamic Cooperation (OIC) over the period 2000–2022, this research applies a fixed effects model with Driscoll–Kraay standard errors. Unlike prior studies that treat the Muslim world as a homogeneous entity, this study disaggregates the sample into four regions: the Middle East and North Africa (MENA), Sub-Saharan Africa (SSA), Southeast Asia (SEA), and South Asia (SA). The sub-sample analyses reveal notable variations: the effect is weakly positive in MENA, attributable to rentier patriarchy; significantly negative in SSA, where subsistence economies force women into informal sector employment without social protection; and significantly positive in both SEA and SA. These findings underscore the necessity of accounting for regional heterogeneity, which in turn shapes the gender regime across different regions of Islamic presence. Consequently, the progressivity of women's roles and the observed outcomes of their participation are contingent upon a constellation of complex factors, including religious normative values, social norms, and economic structures.